2024
DOI: 10.1002/cac2.12534
|View full text |Cite
|
Sign up to set email alerts
|

N6‐methyladenosine reader hnRNPA2B1 recognizes and stabilizes NEAT1 to confer chemoresistance in gastric cancer

Jiayao Wang,
Jiehao Zhang,
Hao Liu
et al.

Abstract: BackgroundChemoresistance is a major cause of treatment failure in gastric cancer (GC). Heterogeneous nuclear ribonucleoprotein A2B1 (hnRNPA2B1) is an N6‐methyladenosine (m6A)‐binding protein involved in a variety of cancers. However, whether m6A modification and hnRNPA2B1 play a role in GC chemoresistance is largely unknown. In this study, we aimed to investigate the role of hnRNPA2B1 and the downstream mechanism in GC chemoresistance.MethodsThe expression of hnRNPA2B1 among public datasets were analyzed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…It has diverse functions in RNA metabolism, including pre-mRNA splicing, mRNA stability, transport, and translation regulation [39]. Recent study has indicated that hnRNPA2B1 can serve as an m 6 A reader to stabilize lncRNAs [40]. Brie y, hnRNPA2B1 interacted with and stabilized lncRNA NEAT1 in an m 6 Adependent manner, which contributed to the maintenance of stemness property via Wnt/β-catenin pathway and exacerbate chemoresistance in gastric carcinoma [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has diverse functions in RNA metabolism, including pre-mRNA splicing, mRNA stability, transport, and translation regulation [39]. Recent study has indicated that hnRNPA2B1 can serve as an m 6 A reader to stabilize lncRNAs [40]. Brie y, hnRNPA2B1 interacted with and stabilized lncRNA NEAT1 in an m 6 Adependent manner, which contributed to the maintenance of stemness property via Wnt/β-catenin pathway and exacerbate chemoresistance in gastric carcinoma [40].…”
Section: Discussionmentioning
confidence: 99%
“…Recent study has indicated that hnRNPA2B1 can serve as an m 6 A reader to stabilize lncRNAs [40]. Brie y, hnRNPA2B1 interacted with and stabilized lncRNA NEAT1 in an m 6 Adependent manner, which contributed to the maintenance of stemness property via Wnt/β-catenin pathway and exacerbate chemoresistance in gastric carcinoma [40]. Interestingly, the increased expression of 4930544M13Rik-201 in CCI-ION mice was also countered by the administration of hnRNPA2B1 siRNAs in the TG, but total hnRNPA2B1 was not affected by knocking down 4930544M13Rik-201 or CCI-ION treatment.…”
Section: Discussionmentioning
confidence: 99%